Implementation of Social Science Values in the Kitab al-Nawadhir at Salaf al-Fathimiyyah Islamic Boarding School, Tambakberas, East Java - Firdaus, Mohammad Wildan; Hamdan, Hamdan Tri Atmaja (Kopertais Wilayah X Jawa Tengah, 2025)
The challenges associated with Social Science (IPS) education within mainstream schooling frequently stem from the predominance of cognitive-oriented methodologies that overlook the internalisation of values and the development of social character among learners. This study seeks to investigate the implementation of Social Science values at Salaf al-Fathimiyyah Islamic Boarding School Tambakberas East Java employing the Kitab al-Nawadhir as the primary instructional resource to cultivate values of justice, responsibility, tolerance, and communal cooperation. A qualitative descriptive methodology was utilised, with primary data sourced from the text of Kitab al-Nawadhir and secondary data derived from academic journals, scholarly articles, and pertinent documents. Data were gathered through in-depth interviews with the school’s administrators, Social Science teachers, and selected students. Data analysis encompassed data reduction, thematic categorisation, and narrative interpretation. The findings indicate that the social values embedded in Kitab al-Nawadhir are systematically internalised through collective life practices, institutional guidance, and exemplary behaviour within the boarding school. These results illustrate that the educational model at Salaf al-Fathimiyyah not only integrates narrative content with social experiences and local cultural practices but also presents an effective alternative approach to Social Science education in contemporary educational contexts.